Analisis Karakteristik Curah Hujan di Wilayah Kabupaten Banjar - Eddy Nashrullah (Lambung Mangkurat University Press, 2023)
The characteristics of rainfall in Banjar Regency can be known by analyzing the rainfall data that occurred in Banjar Regency. To conduct rainfall analysis, the data was obtained from the Banjar Regency Central Bureau of Statistics, which is contained in the Banjar Regency in Figures from 2014 to 2023. The data that used in this analysis is maximum rainfall data. The research method that used in this analysis is frequency analysis to determine the suitable distribution method to be used based on the available data. Based on the analysis, it was found that the distribution method that meets the requirements for analyzing design rainfall is the Log Person III method. The design rainfall for a 2-year return period is 456.6607 mm, for a 5-year return period is 603.5907 mm, for a 10-year return period is 713.0071 mm, for a 25-year return period is 1178.534 mm, for a 50-year return period is 990.5573 mm, and for a 100-year return period is 1125.165 mm. Using the Monobe method, an analysis is conducted to determine the rainfall intensity for each return period. The highest rainfall intensity is estimated to occur at the 25-year return period, which is 408.575 mm. It is expected that this research can help the local government and the community to be considered as a basis for flood control building planning in Banjar Regency